Technocrats vs. tipping points: How East Asian governance shapes global emissions - Joseph Lavallee; Bruno Di Giusto (PLoS ONE, 2026)
Why do East Asian economies—China, Japan, South Korea, and Taiwan—lag behind expectations in climate mitigation despite their technological prowess and economic strength? To approach this question, we extend Lamb and Minx’s “architectures of constraint” framework through an integration of civic engagement and political representativeness metrics. Using principal component and cluster analyses across 28 countries responsible for 70% of global carbon emissions, we uncover six distinct climate policy architectures, notably identifying a unique East Asian developmental state cluster. This cluster features powerful bureaucracies and state-business alliances but weak civic-participatory channels, creating institutional bottlenecks that prevent public environmental concern from translating into robust climate policies. Challenging the prevailing view that democratization alone ensures ambitious climate action, our study suggests that the channels through which citizens influence policy are closely linked to climate outcomes. Given East Asia’s enormous share of global emissions, our findings have urgent implications for international climate governance strategies. To accelerate the global energy transition, tailored strategies that address East Asia’s distinct institutional dynamics are critical.